Penentuan Gerakan Bantu pada Penyanyi Sopran untuk Mencapai Nada Tinggi diatas Aâ Menggunakan Principal Component Analysis yang Ditinjau dari Aspek Ergonomi (Studi Kasus di Paduan Suara Mahasiswa Universitas Kristen Maranatha) - ., Andrijanto; Jonathan S., Benny (Zenit, 2014)
Singing can be done either individually or together in a choir. However, they ways to sing individually and in a choir are not the same. In a choir, singers are divided into four groups, nemely sopran, alto, tenor, and bass. Sopran singers are females, and they are expected to be able to reachC” note. There are several physical movements that can be used to make singers reach notes above A’. This research intends to find out which movements can help the singers to be able to reach high notes without feeling tired. Five movements were used for this purpose. The heart beats of sopran singers are measured while singing C-C” notes, accompanied by the piano and used five movements alternately. The energy consumption and the highest note to reach when using the movements will be analyzed. The energy consumption of each movement was calculated by referring to to the heart beatsand the ranks by using Principal Component Analysis (PCA). This research will conclude that there are efficient movements to use for singing several songs, and reaching the highest note.Keywords: choir, sopran singers, energy consumption, ergonomy